Column Level Uni -Temporal Data - Kvet, Michal; Matiasko, Karol (Communications - Scientific letters of the University of Zilina, 2014)
The basic paradigm of conventional database systems is based on the current valid data processing. However, today’s database systems should provide also management for historical and future valid data. Standard temporal model, using object level, stores the whole object data after the insert or update operation, although only some attributes changed their values. This paper deals with the principle of temporal data modelling based on the column level, not the whole object, describes the structure and principles of required methods, procedures, functions and triggers to provide functionality of the system. All designed and implemented solutions are compared with the existing solutions.